Incorporation of elevator evacuation from a specific floor – A numerical study of an office building - Hammarberg, Johanna; Niva, Håkan; Mossberg, Axel (Collective Dynamics, 2020)
This paper investigates evacuation from a specific floor plan to determine if elevators can replace one of the escape routes consisting of a staircase without lengthening the evacuation times. This study specifically studies evacuation from one single office floor with 360 and 540 occupants, designed as one fire compartment with an area of 2800 m2. To specify the occupants’ willingness to use the elevator for evacuation from different floors, three different functions are used. These functions are modified to include more floors and are used to derive different distributions for the proportion using staircases and elevators, by simulations in Pathfinder. Two setups are studied. First, three staircases are used for evacuation. Secondly, one staircase is replaced with five evacuation elevators with capacity for eight occupants, and one elevator for sixteen occupants. For these setups, evacuation is studied from the 2nd, 8th, 16th, 25th and 50th floor. In addition to the studied functions, distributions that minimize the evacuation time for each floor are derived from the simulations. These distributions give the shortest possible evacuation times. The distributions are then compared to evacuation simulations from the first setup, only utilizing the three staircases. The results show that for the elevators to fully replace a staircase, between 45-60 % of the floor occupants need to use the elevators when the occupant count is 360, and 43-50 % when the number of occupants is 540. However, these values are dependent on floor number. Compared to the functions studied, the optimal percentage is significantly higher for lower floors, becoming closer to the functions as they increase with higher floor numbers. For each distribution on every floor, queuing time was also studied. Based on the results from the calculations, the study concludes that six evacuation elevators could replace one staircase on the studied office floor. However, this result relies on a certain percentage of the occupants using elevators for evacuation.